Survey of verbalized types of precedent phenomena in the TV debates (by materials of debates between P. Poroshenko and V. Zelenskyi) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2019)
The article deals with linguistic aspect of the election debate between P. Poroshenko and V. Zelenskyi, throw the analysis of verbalized precedent phenomena (the precedent texts and the precedent situations). It is defined the place and peculiarities of TV debates in political discourse. Special attention was paid to specific Ukrainian features of this dialogical form of election discourse. It should be stressed that choosing the precedent phenomena as the subject of this investigation is based on their distinction.Precedent phenomena is considered like the most capacious linguistic unites for cultural, national, cognitive and emotional information; like the most compact language structures with the biggest suggestive and persuasive potential in modern Ukrainian-speaking political discourse. Precedent texts’ and precedent situations’ characteristics of typology and meaning were analyzed. There were studied the ways for realizations of verbalized types of precedent phenomena in oral political speech. The paper described such forms of realization mentioned precedent unites like precedent name, precedent expression, describing verbalization and others. The author raised the problem of enlistment describing verbalization to precedent phenomena like one of the realization form of precedent text and / or precedent situation. It is proposed to classify some non-predicative language structures as precedent expression (for example set expressions or another constant speech compounds).
Keywords: precedent phenomenon; precedent situation; precedent text; political discourse; TV debate